THE CORRELATION BETWEEN THE LOCATION OF THE TUMOR TOWARDS HEMOGLOBIN LEVEL AND ERYTROCHYTE INDEX VALUE IN COLORECTAL CANCER PATIENTS AT RSUP PROF. DR. I.G.N.G. NGOERAH - Pramesti, Ardhia Gita; Ayu Dewi, Ni Nyoman; Winarsa Ruma, I Made; Wihandani, Desak Made (E-Jurnal Medika Udayana; Vol 13 No 10 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i10.P01, 2024)
One of the most often found clinical manifestation of colorectal cancer is anemia. If anemia is One of the most often found clinical manifestation of colorectal cancer is anemia. Worse response to the treatment, disease free period, locoregional control, and overall survival is predicted if anemia is present before the treatment. In elucidating the etiology of anemia, the erythrocytes index (MCV, MCH, MCHC) are useful. The hemoglobin level and erythrocyte index value in colorectal cancer patients is affected by a few factors. One of the most significant factor is the location of the tumor.  The objective of this paper is to determine the correlation between location of the tumor towards hemoglobin level and erythrocyte index value in colorectal cancer patients at RSUP Prof. Dr. I.G.N.G. Ngoerah. The study design of this research was a cross sectional study. The data that used were taken from medical records of patients with colorectal cancer in RSUP Prof. Dr. I.G.N.G. Ngoerah from the period of January 2021 until December 2022. A total of 58 patients were met the inclusion criteria. The hemoglobin level and erythrocytes index value were obtained from the blood routine results of colorectal cancer patients. The hemoglobin level used to determined the severity of anemia, which classified into normal, mild anemia, moderate anemia, and severe anemia. Tumor location is divided into two, left-sided and right-sided. The chi square bivariate test is used as hypothesis test, and Kolmogorov-Smirnov test is used as alternative test. The majority of the age of the subjects are middle-age adults patient (41-60 years old), contributes 50% of all subjects. The colorectal cancer patients who experienced anemia were 74.1% (43/58). The colorectal cancer patients who had low MCV were 36.2% (21/58), low MCH 50% (29/58), and low MCHC 65.5% (38/58). The tumor location of the colorectal cancer is significantly correlated with hemoglobin level (p= 0.004). The tumor location is not significantly correlated with erythrocyte index; MCV, MCH, and MCHC (p=0.674, p=0.979, p=0.180). Keywords : Colorectal Cancer, Tumor Location, Anemia